(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Recently there is increasing interest in using optical fiber links to distribute impulse radio-ultrawideband (IR-UWB) signals in order to increase the coverage area. This paper investigates the transmission performance of these signals over existing fiber links and addresses the possibility of increasing the coverage area beyond 30 km.The transmission link consists of a single- mode fiber, dispersion compensating fiber (DCF) and, optical amplifiers. Simulation results are presented using Optisystem (version 13.0) software package for both Gaussian monocycle and 5th-order derivative Gaussian systems, each operating with ON-OFF keying (OOK) and biphase modulation (BPM) formats. The results reveal that extending the coverage area for 625 Mb/s UWB signal toward 100 km is possible for the UWB signals and modulation formats adopted in this study.